THE DEVELOPMENT OF HEALTH-IMPROVING TOURISM IN KAZAKHSTAN - YESSENGABYLOVA, Aiman; SURAGANOVA, Sairan; BISSEKOV, Alken; ZHUNUSSOVA, Gulshat; REY, Inna (Journal of Environmental Management and Tourism, 2016)
The purpose of this study is to provide an overview of the theoretical background and practical recommendations for refining the development of health-improving tourism in Kazakhstan on the example of Almaty region. The article analyzes the state of development, problems and their solutions, as well as current perspectives of health-improving tourism in Kazakhstan.The study used the methods of the analysis of scientific literature and statistical methods, and applied the complex logical approaches to the study of the health-improving industry. The research provides the detailed author’s definition of health-improving tourism, based on the analysis of the conceptual framework; analyzes the current state of the market of relaxation and spa services in Kazakhstan; presents the results of the analysis of sanatorium-and-spa resorts of Almaty region of Kazakhstan; formulates some recommendations on improving the government regulation of health-improving services. The obtained results can be applied for improving the functioning of sanatorium-and-spa resorts in Kazakhstan, as well as developing the tourism organizations and other institutions related to the market of health-improving tourism.The issue of health-imporoving tourism in Kazakhstan is underdeveloped in scientific literatureas in Kazakhstan as well as abroad. All information presented in article is unique and based on the newest data.
Keywords: health-improving tourism; Kazakhstan; recreation; medical tourism; resort